Reflexive translation studies : translation as critical reflection - Kadiu, Silvia (Literature and translation., 2019)
In Reflexive Translation Studies, Silvia Kadiu investigates the viability of theories that seek to empower translation by making visible its transformative dimension; for example, by championing the visibility of the translating subject, the translator's right to creativity, the supremacy of human translation or an autonomous study of translation.